Features and specificities of the regional rural development in the Republic of Serbia - Nikezić, Srđan; Matić, Milutin (Economics of Agriculture, 2010)
All rural areas in the Republic of Serbia, and overall life, work and development in our country, have a number of its characteristics and peculiarities. It is primarily expressed in the great wealth of natural and human resources, and through various economic activities, with significant material and cultural goods and more, with distinct characteristics, trends and diversity in some areas or regions in our country. In addition, it should be noted that in Serbia in all areas, including the rural, there is enormous potential for a better life and work, as well as for the overall development and progress. However, due to various factors, and most often personal, peripheral and irrelevant, it's mostly been implemented or are now doing. For this reason, among others, and today there are significant disparities and imbalances in economic, technological, social, cultural and other levels of organization and development between different parts of Serbia - from north to south and from west to east of the country, which certainly can and must mitigate or overcome in a different environment and circumstances, which the authors wish to point out in this paper.